Pengembangan Bahan Ajar Berbasis Digital Menggunakan Aplikasi Heyzine Flipbooks Tentang Kesultanan Banten Abad Ke-17 Di Kelas X Smkn 2 Kota Serang - Ramadhani, Denisa; Nurhasanah, Ana; Fadillah, Mohammad Ali (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
The aim of this development research is to analyze the need for developing digital-based teaching materials using the Heyzine Flipbooks application about the 17th century Sultanate of Banten at SMKN 2 Kota Serang and to analyze the results of the feasibility test for digital-based teaching materials using the Heyzine Flipbooks application about the 17th century Sultanate of Banten at SMKN 2 Kota Serang, with research subjects from Class X TM 1 which was carried out with a total of 42 students. The method used is Research and Development (R&D) with the ADDIE Model approach consisting of 5 components including: Analysis, Design, Development, Implementation, Evaluation. The suitability of teaching materials is known after being validated by experts, namely material experts, media experts and language experts. The results of the research show that the appropriateness level of teaching materials in terms of material for material experts is 85.26%, this percentage is included in the good category so that it is "usable". Then the suitability of teaching materials in terms of language has the same percentage, namely 83%, both percentages are included in the good category so they are "usable". Meanwhile, the suitability of teaching materials in terms of media for media experts is 88.88%, this percentage is included in the good category so that it "can be used". Trials limited to small groups of students obtained results of 86.25%, this percentage is included in the very good category so it is "usable". Then, in a limited trial on large groups of students, results were 87.5%, this percentage was included in the very good category so it was "usable". Keywords: Teaching Materials, Digital Based, Sultanate of Banten.